Food and beverage can lids

A specially formulated aluminum alloy can lid with controlled composition and score morphology addresses the challenges of recycling 3000 series aluminum into can lids, ensuring strength and corrosion resistance, thus reducing environmental impact.

JP7610648B2Active Publication Date: 2025-01-08TOYO SEIKAN KAISHA LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023095460
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-25
Filing Date
2023-06-09
Publication Date
2025-01-08
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The recycling of aluminum beverage cans into can lids is challenging due to the composition mismatch between recycled 3000 series aluminum alloys and the required 5000 series alloys, leading to issues such as decreased score strength, unintentional breakage, microcracks, and corrosion, which are exacerbated by increased Al-Fe-Mn-Si crystallized substances.

Method used

A can lid made from an aluminum alloy with specific compositions of Mn, Mg, Si, Fe, Cu, Cr, Zn, and Ti, along with controlled thickness and score morphology, is used to enhance strength, prevent breakage, and improve corrosion resistance, even when made from recycled materials.

Benefits of technology

The solution provides a can lid with enhanced pressure resistance, reduced unintentional breakage, and improved corrosion resistance, effectively utilizing recycled aluminum while maintaining performance comparable to new materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610648000012
    Figure 0007610648000012
  • Figure 0007610648000013
    Figure 0007610648000013
  • Figure 0007610648000014
    Figure 0007610648000014
Patent Text Reader

Abstract

To provide a can lid with an end and / or a tab having performances including pressure resistance required for the can lid even when it contains a recycled aluminum alloy which uses aluminum UBC as a raw material.SOLUTION: Provided is a food or beverage can lid that includes an end and a tab, the end being formed with an opening scheduled part which is defined by a breakable score, and the tab being attached by a rivet, wherein the end and / or the tab is made of an aluminum alloy containing Mn: 0.5 to 1.4 mass%, Mg: 2.0 to 4.5 mass%, Si: 0.6 mass% or less, Fe: 0.8 mass% or less, Cu: 0.25 mass% or less, Cr: 0.10 mass% or less, Zn: 0.25 mass% or less, Ti: 0.10 mass% or less, and the end and the tab are composed of the same aluminum alloy.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy can lid consisting of an end and a tab for tearing open a score formed in the end, and more specifically to a can lid for food and beverages that uses recycled material made from aluminum cans after consumption of their contents and yet has the performance required for the end and tab. [Background technology]

[0002] Food and beverage cans, which are made of a can body made of a metal such as aluminum or steel and an aluminum can lid attached thereto, are widely used as cans for filling with beverages such as beer or soft drinks, or foods. Such aluminum can lids generally consist of an end and a tab for tearing a score formed in the end to form an opening defined by the score. Materials used for can lids are required to have strength, formability, corrosion resistance, etc. That is, the ends must have excellent pressure resistance so that the can lids do not deform, even in the case of positively pressurized cans containing carbonated beverages or the like, or in the case of negatively pressurized cans where the pressure is reduced due to a drop in temperature caused by filling the cans at high temperatures, and must have toughness so that the scores do not break unintentionally. On the other hand, the tabs must have breaking strength and toughness so that they do not break or tear when forming an opening.

[0003] As an example of an aluminum alloy used for can ends, Patent Document 1 listed below proposes an aluminum-magnesium alloy that does not contain beryllium, and is characterized in that it contains 0.8 to 15 mass% Mg and 0.2 to 0.6 mass% Fe, the total content of Al and Mg is 90 mass% or more, and the content of P as an impurity is 0.001 mass% or less. Furthermore, the following Patent Document 2 describes a cold-rolled sheet material having a thickness of 0.22 to 0.25 mm, which is made of an aluminum alloy containing, by mass, 0.80 to 1.50% Mg, 0.80 to 1.20% Mn, 0.40 to 0.60% Fe, 0.20 to 0.40% Si, and 0.15 to 0.25% Cu, and which satisfies the content relations of Mn / Fe=1.5 to 2.5 and Mg / Mn≧1.0, with the remainder being aluminum and unavoidable impurities; The aluminum alloy sheet for negative pressure can ends is characterized in that one or both sides thereof are covered with an organic resin film, and that after paint baking, the 45° earing is 1.5 to 3.0%, the 0-180° earing is 1.0 to 2.5%, and the formula: -0.6%≦(45° earing)-(0-180° earing)≦1.5%, and further the tensile strength in the direction at 0° to the rolling direction is 270 to 300 MPa and the proof stress is 240 to 270 MPa. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5920705 [Patent Document 2] Patent No. 5898426 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, nearly 100% of used beverage cans (hereinafter sometimes referred to as "UBC") after the contents have been consumed are collected, and aluminum beverage cans are regenerated into aluminum ingots and recycled. While 3000 series aluminum alloys with a high Mn content are generally used for the can bodies, 5000 series aluminum alloys with a high Mg content, which are stronger than 3000 series aluminum alloys, are used for the can ends (ends and tabs) from the viewpoints of strength, formability, corrosion resistance, etc. Therefore, recycled aluminum alloys made of UBC have a composition close to that of 3000-series aluminum alloys, which account for a large proportion of the total weight of aluminum beverage cans, and have a higher Mn content and a lower Mg content than 5000-series aluminum alloys, making them difficult to use for can ends, and new aluminum ingots have had to be used for can ends. However, the production of new aluminum ingots requires a large amount of electricity, which results in large carbon dioxide emissions, and from the perspective of the environmental burden, there is a demand for the use of recycled materials in can ends as well.

[0006] In addition, in aluminum alloys with a high Mn content using recycled aluminum alloys made of UBC, the strength of the score formed on the end decreases due to an increase in Al-Fe-Mn-Si crystallized products, so that the score may break unintentionally when subjected to a drop impact, resulting in leakage of contents. It was also found that microcracks may occur in the organic coating on the inner side of the score processing part (inner side of the end) and the rivet forming part for attaching the tab, which may cause metal exposure and corrosion of the end due to storage over time. Furthermore, in aluminum alloys with an increase in Al-Fe-Mn-Si crystallized products, the toughness is reduced, making them prone to cracking, and there is a risk that the score may derail and break when breaking the score to form an opening. In addition, the tab attached to the end is generally made of a thin plate for ease of forming an opening and for the strength of the tab, and the end is shaped by bending the gripping part for the fingers and curling the other parts. In this case, if an aluminum alloy with an increased amount of Al-Fe-Mn-Si crystallized matter is used, there is a risk of the tab breaking or cracks occurring on the metal surface of the processed part.

[0007] Therefore, an object of the present invention is to provide a can lid having an end and / or a tab that has the pressure resistance and other properties required for a can lid, even if it contains recycled aluminum alloy made from aluminum UBC. Another object of the present invention is to provide a can lid having an end and / or a tab which has high score strength, effectively prevents leakage of contents due to unintended breakage of the score and effectively prevents the occurrence of microcracks in the organic coating due to score processing, and is also effectively prevented from breakage at locations other than the score, even when the can lid is formed from a material containing a recycled aluminum alloy made from aluminum UBC having a high Mn content and a large amount of Al-Fe-Mn-Si system crystallized matter. [Means for solving the problem]

[0008] According to the present invention, there is provided a can lid for food and beverages, which comprises an end and a tab, the end having a breakable score formed therein which defines a planned opening portion, and the tab being attached with a rivet, characterized in that the end and / or the tab are made of an aluminum alloy containing 0.5 to 1.4 mass% Mn, 2.0 to 4.5 mass% Mg, 0.6 mass% or less Si, 0.8 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti, and the end and the tab are made of the same aluminum alloy.

[0009] In the food and beverage can lid of the present invention, (1) The aluminum alloy contains 0.5 to 1.0 mass% Mn, 3.0 to 4.5 mass% Mg, 0.60 mass% or less Si, 0.8 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti. (2) The aluminum alloy contains 0.5 to 1.0 mass% Mn, 3.0 to 4.5 mass% Mg, 0.35 mass% or less Si, 0.6 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti. (3) The aluminum alloy contains 0.5 to 1.0 mass% Mn, 2.0 to 3.0 mass% Mg, 0.60 mass% or less Si, 0.8 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti. (4) The aluminum alloy contains 0.5 to 1.0 mass% Mn, 2.0 to 3.0 mass% Mg, 0.35 mass% or less Si, 0.6 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti. (5) The Mg content in the aluminum alloy is 2.0 to 3.0 mass%, and the remaining thickness of the score at the initial opening portion of the score is 71% or less of the original sheet thickness. (6) The aluminum alloy An aluminum alloy consisting of The tensile strength of the plate in the rolling 0° direction after paint baking is 350 to 410 MPa. (7) The thickness of the non-processed portion of the end is 0.19 to 0.30 mm, and the thickness of the non-processed portion of the tab is 0.24 to 0.35 mm. (8) The aluminum alloy contains recycled aluminum beverage cans. (9) The Mn content of the aluminum alloy is 0.8 to 1.4 mass%. is preferred.

[0010] The present invention also provides a food / beverage filled can, which is characterized in that the above-mentioned food / beverage can lid is applied to a can filled with food / beverage. Effect of the Invention

[0011] According to the food and beverage can lid of the present invention, even if a recycled aluminum UBC is used, the main components of the alloy elements are within the above ranges, so that an end having excellent pressure resistance and a tab having excellent breakage resistance can be obtained. This makes it possible to reduce the amount of new aluminum used, which generates a large amount of carbon dioxide emissions. Furthermore, in the food and beverage can lid of the present invention, even if the Mg content in the recycled aluminum UBC material is in a range different from that of the 5000 series aluminum alloy, strength can be obtained due to the Mn contained in the recycled material, and by specifying the original plate thickness (non-processed portion) of the end and the remaining thickness in the initial opening portion of the score processing portion, a can lid can be provided that does not impair the performance required of a can lid, such as pressure resistance and openability.

[0012] In the present invention, by improving the form (shape, size, etc.) of the breakable score (main score) formed in the end, even an end made of a recycled aluminum alloy made from aluminum UBC in which Al-Fe-Mn-Si-based crystallized matter increases has high score strength, and unintended breakage of the score is effectively prevented even when it is subjected to a drop impact, etc. In addition, the occurrence of microcracks in the organic coating on the back surface of the score processing part (inner surface side of the end) and the top surface of the rivet is effectively prevented, and an end with excellent corrosion resistance can be provided. Furthermore, when the score breaks, breakage (derailment) of parts other than the score and the so-called pop missile phenomenon at the time of initial opening do not occur, and the openability is also excellent. In addition, by improving the thickness of the curled portion and the finger loop portion formed by bending as described above for the tab attached to the score, it is possible to effectively prevent cracks from occurring on the metal surface of the tab and scratches on the rivet when attaching the tab to the end while maintaining excellent opening properties.

[0013] Furthermore, according to the manufacturing method of the end of the present invention, even when using aluminum UBC which has a high Mn content and is prone to increase Al-Fe-Mn-Si based crystallized products, it is possible to form a score with high score strength as described above. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 shows an example of a can lid of the present invention, where (A) is a plan view and (B) is a cross-sectional view. [Diagram 2] FIG. 4 is a partially enlarged cross-sectional view for explaining the score processing portion of the end. [Diagram 3] 1 is a diagram for explaining the score processing portion of the end, and is a partially enlarged cross-sectional view of an axial cross section in the width direction of the score. [Figure 4] FIG. 4 is a partially enlarged cross-sectional view for explaining the amount of metal displacement of the main scores and the auxiliary scores. [Diagram 5] FIG. 2 is a partially enlarged cross-sectional view showing an axial cross-section in the length direction of the score. [Figure 6] FIG. 11 is a partially enlarged plan view illustrating a score formed in the vicinity of a tab attachment portion by a rivet. [Figure 7] FIG. 4 is an enlarged cross-sectional view of a rivet forming portion. [Figure 8] 1 is a cross-sectional photograph of a tab attachment portion. [Figure 9] 1A and 1B are diagrams showing an example of a tab used in the present invention, in which (A) is a plan view and (B) is a cross-sectional view. [Figure 10] FIG. 2 is an explanatory diagram of a score forming blade used in the manufacturing method of an end cap of the present invention, and is an enlarged cross-sectional view of a width direction cross section of the score forming blade. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] (Aluminum alloy) An important feature of the can lid for food and beverages of the present invention is that the aluminum alloy constituting the end and / or tab of the can lid contains 0.5 to 1.4 mass% Mn, 2.0 to 4.5 mass% Mg, 0.6 mass% or less Si, 0.8 mass% or less Fe, 0.10 mass% or less Cr, 0.25 mass% or less Zn, 0.10 mass% or less Ti, and 0.25 mass% or less Cu. As described above, the recycled material made of aluminum UBC has an alloy composition similar to that of a 3000 series aluminum alloy, since the can body made of a 3000 series aluminum alloy with a small amount of Mg and a large amount of Mn accounts for a large portion of the recycled material. However, in the end and tab of the can lid of the present invention, even when such a recycled material is used, since the aluminum alloy has the above alloy composition with an adjusted amount of Mg, it is possible to provide an end without deformation of the lid and a can lid in which the tab is effectively prevented from breaking when opened, even when the end and tab of the can lid contain such a recycled material made mainly of a 3000 series UBC.

[0016] In the above aluminum alloy constituting the end and / or tab, the Mn content is preferably in the range of 0.5 to 1.4 mass %, particularly preferably 0.5 to 1.0 mass %. That is, Mn is an essential element for improving the strength of an aluminum alloy. However, if the Mn content is too high, the amount of Al-Fe-Mn-Si crystals increases, thereby decreasing toughness. This reduces the score strength at the ends, which may cause the scores to break unintentionally. Also, when it comes to tabs, they may break or tear when openings are formed, and their repeated bending resistance may decrease. Furthermore, Mg is an essential element for obtaining the strength required for can ends, such as tensile strength, proof stress, and elongation, and if the Mg content is too low, the ends may be deformed when subjected to positive pressure canning or sterilization treatment, and the tab breaking strength may be reduced. If the Mg content is higher than the above range, there is a risk of ingot cracking and cracking during hot rolling and can end forming. Therefore, even if the Mn and Mg contents are within the above ranges, when the Mn content is high and Al-Fe-Mn-Si crystals are likely to be abundant, the tensile strength and other properties of the aluminum alloy can be appropriately complemented by setting the Mg content to 2.0 to 3.0 mass%, and it becomes possible to have excellent pressure resistance while suppressing cracking during forming. On the other hand, in an aluminum alloy with a relatively small Mn content, a Mg content of 3.0 to 4.5 mass% similarly makes it possible to have excellent pressure resistance.

[0017] Regarding Si and Fe, they form the above-mentioned Al-Fe-Mn-Si crystals, and act as recrystallization nuclei during hot rolling to form crystal grains of various orientations, suppressing concentration in the Cube orientation at the end of hot rolling. From this viewpoint, it is preferable that Si is 0.6 mass% or less, particularly 0.35 mass% or less, and Fe is 0.8 mass% or less, particularly 0.6 mass% or less. Cu and Cr are contained to increase the strength of the aluminum alloy. However, if the Cu content is higher than the above range, cracks may occur during hot rolling, and if the Cr content is higher than the above range, coarse intermetallic compounds may be formed. Furthermore, Zn and Ti are impurities that are inevitably contained in aluminum alloys, and so long as they are below the above-mentioned values, they have no effect on the can lid of the present invention.

[0018] In addition, in the can lid of the present invention, as described above, by appropriately adjusting the Mg content according to the Mn content, the strength of the can owing to the Mn contained in the recycled material can be ensured, and as will be described later, by adjusting the remaining score thickness at the initial opening portion of the score processing portion formed on the end, it is possible to use the can lid without unintended score breakage or tab breakage.

[0019] The aluminum alloy constituting the end and / or tab is adjusted to the above alloy composition by adding Mg to the recycled material made of aluminum UBC and, if necessary, adding new aluminum. As described above, the recycled material made of aluminum UBC is mainly made of the 3000 series aluminum alloy that constituted the can body, and therefore contains 0.5 to 1.4 mass% of Mn. In addition to the recycled material made of aluminum UBC, scrap materials discharged in the aluminum alloy sheet manufacturing process and the aluminum can manufacturing process can also be used as the recycled aluminum material.

[0020] The aluminum alloy sheet used for forming the end and / or tab of the can lid of the present invention is produced by melting recycled aluminum and, if necessary, new aluminum, adjusting the amount of alloy components such as Mg, and then carrying out hot rolling and cold rolling, as described above. It is preferable to carry out intermediate annealing during the cold rolling. The above aluminum alloy plate may be subjected to various surface treatments as required by conventional methods, and then a thermoplastic resin coating or an organic coating such as a coating film may be formed by conventional methods. Examples of the surface treatment include, but are not limited to, conventionally known surface treatments such as chromate phosphate treatment and chemical conversion treatments mainly containing oxides of zirconium and / or titanium.

[0021] Examples of thermoplastic resin coatings include olefin resin films such as polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic ester copolymer, ionomer, etc., polyester films such as polyethylene terephthalate, polyamide films such as nylon 6, nylon 6,6, nylon 11, nylon 12, etc., polyvinyl chloride films, polyvinylidene chloride films, etc. Such thermoplastic resin films may be unstretched or biaxially stretched. Examples of paints capable of forming a coating film include modified epoxy paints such as phenol-epoxy and amino-epoxy, vinyl chloride-vinyl acetate copolymers, saponified vinyl chloride-vinyl acetate copolymers, vinyl chloride-vinyl acetate-maleic anhydride copolymers, epoxy-modified, epoxyamino-modified, and epoxyphenol-modified vinyl paints or modified vinyl paints, acrylic paints, and synthetic rubber-based paints such as styrene-butadiene copolymers.

[0022] The aluminum alloy sheet used for forming the end and / or tab of the can lid of the present invention preferably has a tensile strength in the rolling 0° direction of 350 to 410 MPa, particularly 370 to 400 MPa, in a state of a painted aluminum alloy sheet painted and baked with an epoxy-based paint, a polyester-based paint, or the like. When the tensile strength is within the above range, the sheet can also be used as a can lid for a positively pressurized can. The thickness of the aluminum alloy plate is not limited to this, but the plate thickness as an end material is preferably in the range of 0.19 to 0.30 mm, and the plate thickness as a tab material is preferably in the range of 0.24 to 0.35 mm. In the present invention, it is most preferable that both the end and the tab are made of an aluminum alloy having the above-mentioned composition, and it is preferable that at least the end is made of an aluminum alloy having the above-mentioned composition. Also, the end and the tab do not necessarily have to have the same composition, but it is preferable from the viewpoint of productivity and economy that they are made of an aluminum alloy having the same composition.

[0023] (ends and tabs) The can lid of the present invention is not limited in shape, and various shapes can be adopted, so long as it has an end and a tab for breaking a score formed in the end to form an opening. FIG. 1 shows an example of a can lid according to the present invention, where (A) is a plan view and (B) is a cross-sectional view. The can lid, generally designated 1, is a stay-on-tab can lid consisting of an end 2 and a tab 4 fixed to the end 2 by a rivet 3. The end 2 has a circular center panel 21, a chuck wall radius 22 protruding downward from the periphery of the center panel 21, a chuck wall 23 rising from the outer wall of the chuck wall radius 22, and a seaming panel 24 formed continuously with the chuck wall 23. Scores 25 are formed in the center panel 21, and the scores 25 are made up of main scores 25a and auxiliary scores 25b provided inside the main scores 25a. The auxiliary scores 25b are intended to prevent the main scores from cracking during processing, and do not break shallower than the main scores 25a. On the other hand, the tab 4 comprises a tab main body 41, an arc-shaped tab nose 42 formed at a position on the pouring direction side of the contents, a finger hook (grip) 43 formed on the opposite side of the tab nose 42, and a fixing part 44 to which the tab main body 41 is fixed with a rivet 3. The tab main body 41 is also bent at an outer periphery 45 of the grip part 43, and a curl part 46 folded downward is formed around the entire periphery of the outer periphery other than the grip part 43.

[0024] As described above, in the can lid of the present invention, in order to realize the pressure resistance and other properties required for the ends and tabs, it is effective to adjust the Mg content of the aluminum alloy constituting the ends and tabs in accordance with the Mn content. In addition, by adjusting the remaining score thickness in the initial opening portion of the score processing portion formed in the end, it is possible to suppress unintended score breakage and improve the openability, thereby effectively preventing the occurrence of tab tearing and the like. That is, since the initial opening part of the score processing part is located directly under the tab, water droplets may adhere to the part, and since the 5000 series aluminum alloys used for conventional can ends have a high Mg content, they are highly sensitive to moisture and there is a risk of stress corrosion cracking if the remaining score thickness is made thin, but since there is no risk of stress corrosion cracking in aluminum alloys with Mg content in the above range, it is possible to make the remaining score thickness thin at the initial opening part, and opening can be made with light force. On the other hand, aluminum alloys with a high Mn content and a large amount of Al-Fe-Mn-Si-based crystallized substances tend to have poor toughness, and therefore are prone to tab tearing when the tab is opened, but since opening can be made with light force as described above, it is possible to effectively prevent tab tearing even in aluminum alloys with a low Mg content.

[0025] Figure 2 is a partial cross-sectional view showing a schematic representation of the score formation portion of the end. Specifically, as shown in Figure 2, it is desirable to form the scores so that the ratio of the remaining score thickness (thickness of the score processing portion) t1 in the initial opening portion of the score processing portion where the score 25 is formed to the non-processed portion (original plate thickness) t0 of the center panel 21 of the end 2 {(t1 / t0) × 100(%)} is 71%. The ratio of the score remaining thickness to the original end thickness t0 varies depending on the original thickness, and the ratio decreases as the original thickness increases. Specifically, within the range of the original end thickness of 0.19mm to 0.30mm, when the original thickness is greater than 0.190mm and less than 0.200mm, the ratio is 71% or less, when the original thickness is greater than 0.200mm and less than 0.210mm, the ratio is 68% or less, when the original thickness is greater than 0.210mm and less than 0.220mm, the ratio is 64% or less, when the original thickness is greater than 0.220mm and less than 0.230mm, the ratio is 61% or less, and when the original thickness is greater than 0.230mm and less than 0. It is preferable that the thickness is 59% or less when the thickness is greater than 230 mm and less than 0.240 mm, 56% or less when the thickness is greater than 0.240 mm and less than 0.250 mm, 54% or less when the thickness is greater than 0.250 mm and less than 0.260 mm, 52% or less when the thickness is greater than 0.260 mm and less than 0.270 mm, 50% or less when the thickness is greater than 0.270 mm and less than 0.280 mm, 48% or less when the thickness is greater than 0.280 mm and less than 0.290 mm, and 47% or less when the thickness is greater than 0.290 mm and less than 0.300 mm.

[0026] Furthermore, the auxiliary scores, which are formed together with the breakable main scores and are adjacent to and located inward of the main scores, preferably have a remaining thickness ratio of the main scores in the range of from 90% to 50% of the original sheet thickness, and the width thereof is preferably in the range of 50 to 110 μm. The remaining score thickness and score width do not necessarily have to be uniform from the beginning to the end of the score, and can be changed as appropriate depending on the initial opening portion and the position of the score.

[0027] As described above, in the end used in the food and beverage can lid of the present invention, by improving the remaining score thickness and score shape of the breakable score (main score) formed in the end, it is possible to improve the score strength even in an end made of recycled aluminum alloy made from aluminum UBC, which has an increase in Al-Fe-Mn-Si based crystallized matter, and as will be described later, it is possible to effectively prevent the occurrence of microcracks in the organic coating on the back surface (inner surface side of the end) of the score processing portion, derailment when the score breaks, or the so-called pop missile phenomenon when the can is initially opened.

[0028] [Score Shape] As is apparent from FIG. 3, which shows an axial cross section in the width direction of the score, in the end of the present invention, at least a part of the main score 25a has opposing inclined surfaces 26a, 26b in which the score width decreases downward, and a flat surface in the center. Department The inclined surfaces 26a and 26b are continuous with the bottom surface 27 via a curved surface R. Department It is preferable that the width W1 of 27a has at least a portion that is 65% or less of the width W0 of the imaginary bottom surface 27 defined by the imaginary extension lines La, Lb of the inclined surfaces 26a, 26b and the imaginary extension line Lc passing through the center of the bottom surface 27. In this way, the breakable main score is formed so that the inclined surface and the bottom surface are continuous via a curved surface, and the width of the bottom surface (the width of flat portion 27a in the specific example shown in Figure 2) is 65% or less of the imaginary bottom surface. This makes it possible to improve the strength of the score and effectively prevents the score from breaking even when the package is filled with contents and subjected to impact from being dropped or vibration during transportation. That is, as is clear from the results of the examples described later, Department If the width W1 becomes too large, there is a risk that the contents may leak from the score. The width of the bottom surface is the distance at the center of the bottom surface excluding the curved surface connecting the inclined surface and the bottom surface. Department If it has a flat DepartmentThe width of the curved surface is preferably as close to zero as possible, and in this case, the bottom surface is generally arc-shaped and continues from the curved surface. In addition, in the preferred embodiment of the present invention shown in the figures, the inclined surface and bottom surface of the score are continuous via a curved surface, but even if the inclined surface and bottom surface are not connected via a curved surface, the same effect as when a curved surface is connected may be obtained if the remaining thickness of the score is thick or depending on the angle formed by the inclined surface and the bottom surface. In the end of the present invention, the main score has a flat bottom surface. Department From the viewpoint of improving the strength of the score, it is preferable that the portion in which the numerical value is within the above range be formed over the entire area of ​​the main score, but it may also be formed partially in a thin-walled portion where the remaining thickness of the score is small, such as the rear half of the opening.

[0029] The width W0 of the imaginary bottom surface of the score bottom is preferably in the range of 15 to 40 μm, which prevents microcracks from occurring in the organic coating (thermoplastic resin coating or paint film) on the inner surface side of the score (the back side of the end), effectively prevents metal exposure on the inner surface of the end, and makes it possible to provide an end with excellent corrosion resistance. If the width W0 of the imaginary bottom surface is smaller than the above range, there is a risk of stress corrosion cracking, depending on the material used, while if it is larger than the above range, there is a risk of microcracks occurring on the inner surface of the score portion compared to when it is within the above range.

[0030] Furthermore, the score angle Θ formed by the inclined surfaces 26a, 26b of the score is preferably in the range of 40 to 60 degrees. With the score angle Θ in the above range, microcracks do not occur in the organic coating on the inner surface of the score (the back side of the end), metal exposure on the inner surface of the end is effectively prevented, and an end with excellent corrosion resistance can be provided. If the score angle is larger than the above range, there is a risk of microcracks developing in the organic coating on the inside of the score (back of the end), and if the score angle is smaller than the above range, there is a risk that the score blade will become damaged after long-term use, such as chipping of the cutting edge or chipping / cracks from the base.

[0031] [Metal Rejection Amount of Score] As shown in Fig. 1, the end used in the present invention is preferably provided with auxiliary scores adjacent to the main scores and located inward of the main scores, in addition to the breakable main scores. The auxiliary scores are provided to prevent cracking during processing of the main scores, and since they are not breakable themselves, they have a higher score remaining thickness ratio than the main scores, but in the present invention, from the viewpoint of preventing the occurrence of microcracks in the organic coating on the inner surface side of the main scores (the inner surface side of the end), it is preferable to form the auxiliary scores so that the amount of metal displacement S0 due to score processing of the auxiliary scores is 25% or more of the amount of metal displacement S1 due to score processing of the main scores in a cross section perpendicular to the width direction of the score.

[0032] That is, as shown in Fig. 4, the cross-sectional areas S0 and S1 of the main score 25a and the auxiliary score 25b in the cross section perpendicular to the width direction are defined as the metal rejection amount, and it is preferable to form the main score and the auxiliary score so that the ratio [(S1 / S0) x 100] of the metal rejection amount S1 of the auxiliary score 25b to the metal rejection amount S0 of the main score 25a is 25% or more, particularly in the range of 25 to 200%. If the metal rejection amount of the auxiliary score is smaller than the above range, microcracks may occur in the organic coating on the inner surface side of the main score (the inner surface side of the end). Also, even if it is larger than the above range, no defects will occur in the end, but the molding load will increase and there may be a risk of damage to the score forming tool. The amount of rejection of the main score and the auxiliary score does not have to be constant from the beginning to the end of the score, but may vary depending on the location. Furthermore, so long as the proportion of the rejected amount is within the above range, the cross-sectional shape of the score is not important.

[0033] [High score remaining thickness part] As described above, when the pressure inside the can becomes positive pressure, such as in the case of the contents being beer or carbonated beverages, at the initial opening of the score, the planned opening portion is rapidly pushed upward by the gas pressure simultaneously with the release of the internal pressure, and the score is broken. Depending on the force, the so-called pop missile phenomenon may occur, where the planned opening portion separates from the panel portion and is blown away. By providing a high score remaining thickness portion in a part of the main score, such a pop missile phenomenon can be prevented. In the present invention, as shown in FIG. 5 showing the axial cross-section in the score length direction of the main score 25a, a high score remaining thickness portion 28 having a score remaining thickness larger than that of the main score is partially formed in the main score 25a. It is preferable that the score remaining thickness ratio of this high score remaining thickness portion 28 is higher than the score remaining thickness ratio of the main score and 85% or less. That is, as shown in FIG. 5, the score remaining thickness ratio R1 of the main score 25a is the ratio [(t1 / t0)×100(%)] of the main score remaining thickness (t1: the thickness of the score processed portion) to the virtual thickness (t0) when the score 25a is not formed. On the other hand, the score remaining thickness ratio R2 of the high score remaining thickness portion 28 is represented by the ratio [(t2 / t0)×100(%)] of the remaining thickness (t2) in the high score remaining thickness portion. In the present invention, the high score remaining thickness portion is formed so that R1 < R2 ≦ 85%. In addition, the high remaining thickness score portion does not matter the relationship with the main score remaining thickness as long as it is higher than the score remaining thickness ratio of the main score and 85% or less. However, if the step amount from the main score (remaining thickness difference (t2 - t1) in FIG. 2) is too large, the opening operation does not proceed smoothly and the force required for opening increases. Therefore, the remaining thickness difference from the main score is preferably 50 μm or less.

[0034] It is clear from the results of the examples described later that the score can be smoothly broken without derailing when the score remaining thickness ratio is within the above range. That is, when a high score remaining thickness portion with a score remaining thickness ratio of 85% or less is formed, even at the end made of an aluminum alloy containing aluminum UBC with a large Mn content and where Al-Fe-Mn-Si-based precipitates are likely to increase, the score is smoothly broken without the other parts than the score being broken. On the other hand, if the score remaining thickness ratio of the high score remaining thickness portion is greater than the above range, the breaking of the score may stop at the high score remaining thickness portion 28, and the breaking of the end may deviate from this portion and progress. Furthermore, the length of the high score remaining thickness portion in the score length direction (indicated as L in Figure 5) can be changed as appropriate depending on the remaining thickness rate and formation position of the high score remaining thickness portion, the desired pop missile resistance effect, etc., but it is preferable that it is in the range of 3 to 10 μm.

[0035] Fig. 6 is a partially enlarged plan view for explaining the score formed near the tab attachment portion by the rivet 3 in Fig. 1. In Fig. 6, the area A, the outer edge of which is indicated by a dotted line, is the coining process area associated with rivet forming, and the plate thickness in this area is thinner than other areas due to the coining process. As is clear from Fig. 6, the main score 25a and the auxiliary score 25b are formed in the coining process area A, and a high score remaining thickness portion is formed in the main score 25a in the coining process area A, and in Fig. 6, the high score remaining thickness portion is formed from 28a to 28b. The high score remaining thickness portion is formed up to the position 26b located outside the coining process area A, and 28b is a portion where the original plate thickness of the aluminum alloy plate constituting the end is maintained. In the present invention, the remaining thickness ratio of the high score remaining thickness portion is based on the virtual thickness when no score is formed at the location where the high score remaining thickness portion is to be formed, so that even when high score remaining thickness portions are formed at locations with different virtual thicknesses (t0) serving as a reference as shown in Fig. 6, it is possible to form a high score remaining thickness portion that is effective for the main score. In other words, the starting point 28a of the high score remaining thickness portion may be inside or outside the region A. The location and number of the high remaining thickness score portions to be provided are not important, but it is preferable to provide them in the opening initial portion or around the coining region.

[0036] [Blowout prevention score] As mentioned above, if the contents are beer, carbonated drinks, etc., and positive pressure is created inside the can, when the score is initially opened, the intended opening portion is pushed suddenly upward by the gas pressure as the internal pressure is released, causing the score to break. Depending on the force of the blow, the intended opening portion may be separated from the panel portion and blown away, resulting in the so-called pop missile phenomenon. In the end used in the present invention, such a pop missile phenomenon can be prevented by forming a score (a score for preventing eruptions) that crosses the auxiliary score in the vicinity of the initial opening portion of the score and is close to the main score, and has a score remaining thickness ratio of 70 to 90% of the original plate thickness. That is, the auxiliary score is provided to prevent cracks during processing of the main score and does not break itself, and the score in the direction crossing the auxiliary score extends in a direction that blocks the progress of the breakage of the main score due to the release of internal pressure and the rise of the opening planned portion, so that the pop missile phenomenon can be effectively prevented. If the score remaining thickness of this score for preventing eruptions is smaller than the above range, there is a risk of microcracks occurring in the organic coating on the inner side of the score for preventing eruptions (the inner surface of the end), while if the remaining thickness ratio of the score for preventing eruptions is larger than the above range, the pop missile resistance effect cannot be obtained sufficiently. The score for preventing eruptions is provided adjacent to the main score and does not cross the auxiliary score, i.e., it may be provided outside the main score. There are no limitations on the location, but it is preferable to form it in the vicinity of the initial opening portion of the score.

[0037] [rivet] In the end used in the present invention, as described later, a rivet forming portion is formed by rivet forming on a shell formed by pressing an aluminum alloy plate, and then a tab is fitted into the rivet forming portion, and the rivet forming portion is crimped while pressing the top surface of the rivet forming portion, thereby attaching the tab with a rivet. In the end of the present invention, as shown in Fig. 7, it is preferable that the thickness at the center of the rivet forming portion 30 (i.e., the thickness t3 at the center of the rivet forming portion after it is crimped) is 30% or more of the original plate thickness t0. This effectively prevents the occurrence of microcracks in the organic coating at the center of the top surface of the rivet.

[0038] As described above, in the end to which the tab is attached by crimping the rivet forming portion, as shown in Fig. 8, which is an enlarged cross-sectional photograph of the tab attachment portion, the top surface 31 of the rivet forming portion 30 of the end 1 has a central region (indicated by diameter D1 in Fig. 8) that has been subjected to coining processing and is thinner than the surrounding area. In the present invention, the ratio of the diameter D1 of this central region to the inner diameter D2 of the side wall portion 32 of the rivet forming portion 30 [(D 1 / D 2 ) × 100] is preferably 40 to 95%, which effectively prevents the occurrence of microcracks in the organic coating in the rivet forming portion. If the proportion of the central region D1 is less than the above range, there is a risk of microcracks occurring in the organic coating in the central region, whereas if the proportion of the central region is more than the above range, there is a risk of microcracks occurring in the organic coating on the outer edge of the central region D1.

[0039] [tab] In the can lid of the present invention, the tab can be formed from the 5000 series aluminum alloys conventionally used for tabs or the aluminum alloys described above, as described above. In the finger hook portion of the can lid of the present invention, it is preferable that the ratio of the thickness of the finger hook portion to the original sheet thickness (thickness of finger hook portion / original sheet thickness) is 2 or more and is equal to or less than the ratio of the thickness of the curled portion of the tab to the original sheet thickness (thickness of curled portion / original sheet thickness). 9(B) shows an example of a tab applied to a can end of the present invention, where (A) is a plan view and (B) is a cross-sectional view, and as shown in Fig. 9(B), the thickness t4 of finger hook portion (grip portion) 43 and the thickness t5 of curled portion 46 at tab nose 42 due to bending are such that (finger hook portion thickness t4 / original plate thickness t0) is 2 or more and is equal to or less than the ratio of the thickness of the curled portion of the tab to the original plate thickness, which is t0, which is the thickness of the tab material used to form the tab, (curled portion thickness t5 / original plate thickness t0). If the value of t4 / t0 is less than 2, cracks may occur on the metal surface during bending, while if it is greater than t5 / t0, the position of the tab may shift when the rivet forming portion is crimped to attach the tab, making it impossible to insert the tab all the way to the base of the rivet, and thus causing defects in forming, such as scratches on the rivet.

[0040] (End Manufacturing Method) The method for manufacturing the end of the present invention is the same as the conventional method for manufacturing the end, except that a specific score forming blade is used, which will be described later. That is, although not limited to this, a metal plate such as an aluminum alloy plate is punched into a circle in a press forming process, and formed into a shell shape having the above-mentioned seaming panel portion and chuck wall radius portion, and a compound is applied to the groove of the seaming panel portion in a lining process. Next, a cylindrical rivet protrusion is formed, and a score is engraved from the outer surface side of the end in a score forming process. Finally, a tab is fitted into the rivet protrusion, and the head of the rivet protrusion is crimped to attach the tab, thereby manufacturing an end that can be attached to a can body.

[0041] In the present invention, an important feature of the score forming blade used in the score forming step in the above-mentioned manufacturing method is that, as shown in Figure 10, in a vertical cross-section in the width direction of score forming blade 50, it consists of opposing inclined side surfaces 51a, 51b and tip portion 52 located at the lower end of inclined side surfaces 51a, 51b, with the blade width decreasing toward the tip, and that tip portion 52 has at least a portion where width w1 is 65% or less of width W0 of an imaginary tip face defined by imaginary extension lines La, Lb of inclined side surfaces 51a, 51b and an imaginary extension line Lc passing through the center of tip portion 52. The width of the tip is the distance at the center of the tip, excluding the curved surface connecting the inclined side and the tip, and is the distance at the center of the tip, as shown in FIG. Department If it has 52a, it is flat. Department The width of the tip end surface is preferably as close to zero as possible, and in such a case, the tip end surface is generally arc-shaped and continues from the curved surface. In addition, in the preferred embodiment shown in FIG. 10, both sides of the tip 52 are continuous with the inclined side surfaces 51a, 51b via curved surfaces R, but even if both sides of the tip are not connected to the inclined side surfaces or curved surfaces, the remaining score thickness may be increased, or depending on the angle formed by the inclined side surfaces and the tip, the same effect as when a curved surface is connected may be obtained. By using a score blade having the above characteristics when scoring the end, scores are formed that reflect the characteristics of the score blade as described above. This makes it possible to form scores with improved score strength as described above, and also prevents the occurrence of microcracks on the inner surface of the score processing area.

[0042] 10, the imaginary tip width W0 defined by imaginary extension lines La, Lb of inclined side surfaces 51a, 51b of the score forming blade and an imaginary extension line Lc passing through the center of tip 52 of the score forming blade is preferably in the range of 15 to 40 μm. This prevents microcracks from occurring in the organic coating (thermoplastic resin coating or paint film) on the inner surface side of the score portion (the back side of the end), effectively prevents metal exposure on the inner surface of the end, and makes it possible to form an end with excellent corrosion resistance. If the width W0 of the imaginary tip is smaller than the above range, there is a risk of stress corrosion cracking at the end, depending on the material used, while if it is larger than the above range, there is a risk of microcracks occurring on the inner surface of the score portion compared to when it is within the above range.

[0043] Furthermore, it is preferable that the angle Θ of the score forming blade formed by the inclined side surfaces 51a, 51 of the score forming blade shown in FIG. 10 is 40 to 60 degrees. By setting the angle Θ of the score forming blade within the above range, microcracks do not occur in the organic coating on the inner surface of the score portion (the back side of the end), metal exposure on the inner surface of the end is effectively prevented, and it is possible to form an end with excellent corrosion resistance. If the angle of the score blade is greater than the above range, there is a risk of microcracks developing in the organic coating on the inside of the score (back of the end). If the score angle is smaller than the above range, the score blade may become damaged after long-term use, such as chipping of the cutting edge or chipping / cracks from the base.

[0044] In the rivet forming process, as shown in Fig. 7, after fitting tab 4 into shell 2 on which rivet forming portion 30 has been formed, the rivet forming portion is crimped while pressing the top surface of rivet forming portion 30 from above, and the tab is attached to the shell by the rivet. In this case, in the present invention, it is preferable to process so that the processing rate of the original plate thickness at the center of the rivet is 70% or less, particularly in the range of 40 to 70%. In addition, as shown in Fig. 8, in the coining process of the rivet top surface portion, the ratio [(D 1 / D 2 ) × 100] is 40 to 95%, which can effectively prevent the occurrence of microcracks in the organic coating in the rivet forming portion. EXAMPLES

[0045] (Experimental Example 1) Aluminum alloy sheets Nos. 1 to 7 having the compositions shown in Table 1, 5182 material, which is a general-purpose material for end tabs (all of which were subjected to intermediate annealing during cold rolling, sheet thickness: 0.235 mm), and 3104 material, which is a general-purpose material for can bodies (sheet thickness: 0.235 mm), were used to prepare 204 diameter shells, and scores were formed using a score processing tool having a score forming blade (blade width: 35 μm, inclined surface angle: 50 degrees) to prepare ends. Similarly, tabs having the shape shown in FIG. 9 were made using aluminum alloy sheets Nos. 1 to 7, 5182 and 3104 (each with a thickness of 0.235 mm) having the compositions shown in Table 1, and attached to the above-mentioned ends to make can lids. The obtained can lid was attached to the opening of a seamless can, and 350 ml of beer chilled to 5°C was filled into the can.

[0046] [End and tab molding evaluation] For each end obtained as described above, the surface of the chuck wall radius part of the end was microscopically observed to evaluate the end molding defects by marking those with cracks as "x" and those without cracks as "o". The results are shown in Table 1. The surface of the finger loop of each tab obtained as described above was observed under a microscope, and the molding defects of the tab were evaluated by rating those with cracks as "X" and those without cracks as "O". The results are shown in Table 1.

[0047] [Compression strength measurement] A hole was made in the body of the beer-filled can obtained as described above, a tube was connected, and air was pumped in at a pressure increase rate of about 0.33 kgf / cm per second. 2 The peak pressure was 5.5kgf / cm when the lid was inverted. 2 The compressive strength was evaluated by indicating whether the value was greater than the limit with an "O" and whether the value was less than the limit with an "X". The results are shown in Table 1.

[0048] [Table 1]

[0049] (Experimental Example 2) A 204 diameter shell was prepared from an aluminum alloy plate S (Mn: 0.9 mass%, Mg: 2.3 mass%, Si: 0.3 mass%, Fe: 0.5 mass%, Cu: 0.2 mass%, Cr: 0.01 mass%, Zn: 0.14 mass%, Ti: 0.01 mass%) having a thickness of 0.235 mm. A score was formed on the obtained shell in a conventional manner, and a tab was attached to prepare a can lid. The can lid obtained above was attached to the opening of a seamless can, and 350 ml of beer chilled to 5°C was filled into the can.

[0050] [Vibration test] A vibration test was carried out on filled beer cans having the score remaining rate at the initial opening shown in Table 2 under the following conditions using a vibration tester (dynamic vibration tester manufactured by Shinken Co., Ltd.). Vibration direction: can axial direction, vibration frequency: 10Hz, vibration time: 60min, amplitude: 5mm, stack number: 24 cans at 3c / s, can temperature: 30℃, internal pressure: approx. 300kPa Those that did not leak from the scored area were rated as "O", and those that leaked were rated as "X".

[0051] [Inverted drop test] Cans filled with beer having the score remaining rate in the thinnest part shown in Table 3 were dropped end-side down from a height of 150 cm under conditions of a can temperature of 30°C and an internal pressure of approximately 300 kPa, and checked for leakage of beer from the score. Cans that did not leak were rated as "○", and those that leaked were rated as "×".

[0052] [Opening test] For the beer-filled cans shown in Tables 2 and 3, opening formation was performed, and if it opened normally, it was evaluated as "○", and if it did not open normally (it could not be opened initially, it derailed, or it only opened halfway, etc.), it was evaluated as "×".

[0053] [Table 2]

[0054] [Table 3]

[0055] (Experimental Example 3) The 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 and the 204 diameter shell made of 5182 material with a plate thickness of 0.235 mm were scored using a score machining tool with W0 values ​​shown in Figure 3 and Table 4. The ratio of the flat part to the bottom surface (blade width) of the cutting edge was 65%. The surface of the back side of the main score part of the end was checked under a microscope to see if there were any microcracks in the organic coating. Those without microcracks are marked with "○" and those with microcracks are marked with "×" in Table 4. A can lid with a tab attached to the end after scoring was attached to the opening of a seamless can, and 350 ml of beer cooled to 5°C was filled in. The cans were then stored in an environment of 37°C and 80% RH for two weeks. Cans that did not leak were marked with an "O" for resistance to stress corrosion cracking, and cans that leaked were marked with an "X" for lack of resistance to stress corrosion cracking, as shown in Table 4.

[0056] [Table 4]

[0057] (Experimental Example 4) The 204 diameter shell obtained in Experimental Example 2 was scored using a score tool with score angle Θ shown in Figure 3 and shown in Table 5. The ratio of the flat portion to the bottom surface (blade width) of the cutting edge was 65%. The surface of the back side of the main score part of the end was checked under a microscope to see if there were any microcracks in the organic coating. Those without microcracks are marked with "○" and those with microcracks are marked with "×" in Table 5.

[0058] [Table 5]

[0059] (Experimental Example 5) The 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 was formed with main scores and auxiliary scores, each having the displacement amount shown in Table 6, using a score processing tool. Also, a tab made of a 5000 series aluminum alloy plate (5182 material) was attached to prepare a can lid. The surface of the back side of the main score part of the end was checked under a microscope to see if there were any microcracks in the organic coating. Those without microcracks are marked with "○" and those with microcracks are marked with "×" in Table 6.

[0060] [Table 6]

[0061] (Experimental Example 6) The 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2 was formed with auxiliary scores and main scores (score survival rate 50%) for preventing blowout, each having a score survival rate shown in Table 7. A tab made of a 5000 series aluminum alloy plate (5182 material) was attached to produce a can lid. To evaluate the pop missile resistance of the resulting can lid, the can lid was attached to a seamless can, a hole was made in the can body, a tube was connected, and air was applied at a pressure increase rate of approximately 0.33 kgf / cm per second. 2 Pressurize to 5.5kgf / cm while checking the pressure gauge value. 2 The internal pressure was applied until the container was opened. In this state, it was confirmed whether it opened normally. The cases where no pop missiles occurred are indicated by "○", and the cases where pop missiles occurred are indicated by "×". The results are shown in Table 7.

[0062] [Table 7]

[0063] (Experimental Example 7) For the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2, rivets were formed using a press molding machine so that the processing rate of the rivet top surface was the value shown in Table 8. The presence or absence of microcracks in the organic coating at the center of the rivet top surface was confirmed by microscope observation. Table 8 shows that there were no microcracks with "○" and that there were microcracks with "×".

[0064] [Table 8]

[0065] (Experimental Example 8) Regarding the 204 diameter shell (aluminum alloy plate S) obtained in Experimental Example 2, the D shown in FIG. 1 / D 2 The lid was formed using a tool designed to set the values ​​of the ratios shown in Table 9. The organic coating at the center of D1 region and the outer edge of D1 region in Figure 8 was confirmed by microscope observation. Those without microcracks are marked with "○" and those with microcracks are marked with "×" in Table 9.

[0066] [Table 9]

[0067] (Experimental Example 9) Using aluminum alloy sheets S with thicknesses of 0.330 mm and 0.279 mm, tabs with the shape shown in FIG. 9 were formed by varying the thickness of the finger loop (grip) while keeping the tab nose thickness constant as shown in Tables 10 and 11. This tab was attached to the 204 diameter shell (aluminum alloy sheet S) obtained in Experimental Example 1 to create a can lid. The organic coating on the tab finger loop was checked for the presence or absence of microcracks by microscopic observation. Those without microcracks were evaluated as "○" and those with microcracks were evaluated as "×", and the results are shown in Tables 10 and 11. The rivets were also checked for scratches and molding defects. Those without molding defects are marked with "○" and those with scratches or other defects are marked with "×" in Tables 10 and 11.

[0068] [Table 10]

[0069] [Table 11]

[0070] The content disclosed above is such that a person who comes into contact with this disclosure can obtain benefits according to the selected elements by selecting and using elements as appropriate, and can obtain synergistic benefits by combining and using multiple elements. [Industrial Applicability]

[0071] The can lid of the present invention, even when using a recycled aluminum UBC material, can have an end with excellent pressure resistance and a tab with excellent folding and tearing resistance because the amount of alloying elements is adjusted, and can be used for positive pressure cans. In addition, since it is possible to obtain a can lid for food and beverages similar to that obtained when using the new aluminum, it can be suitably used in applications where a reduction in carbon dioxide emissions is required. In addition, by improving the form (shape, dimensions, etc.) of the breakable score (main score) formed in the end, it is possible to provide an end having high score strength, effectively preventing the occurrence of microcracks in the organic coating, and excellent corrosion resistance, even in an end made of a recycled aluminum alloy made from aluminum UBC in which Al-Fe-Mn-Si-based crystallized matter increases. [Explanation of symbols]

[0072] 1 can lid, 2 end, 3 rivet, 4 tab, 21 center panel, 22 chuck wall radius, 23 chuck wall, 24 seaming panel, 25 score, 26 score inclined surface, 27 score bottom surface, 41 tab body, 42 tab nose portion, 43 gripping portion, 44 fixing portion, 46 curl portion.

Claims

1. A lid for a food or beverage can, comprising an end and a tab, said end being formed with a breakable score defining an intended opening portion, and said tab being attached by a rivet, the end and / or the tab are made of an aluminum alloy containing Mn: 0.5 to 1.4% by mass, Mg: 2.0 to 4.5% by mass, Si: 0.6% by mass or less, Fe: 0.8% by mass or less, Cu: 0.25% by mass or less, Cr: 0.10% by mass or less, Zn: 0.25% by mass or less, and Ti: 0.10% by mass or less; A can lid for food or beverage, characterized in that the end and the tab are made of the same aluminum alloy.

2. 2. The food and beverage can lid according to claim 1, wherein the aluminum alloy contains 0.5 to 1.0 mass% Mn, 3.0 to 4.5 mass% Mg, 0.60 mass% or less Si, 0.8 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti.

3. 2. The food and beverage can lid according to claim 1, wherein the aluminum alloy contains 0.5 to 1.0 mass% Mn, 3.0 to 4.5 mass% Mg, 0.35 mass% or less Si, 0.6 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti.

4. 2. The food and beverage can lid according to claim 1, wherein the aluminum alloy contains 0.5 to 1.0 mass% Mn, 2.0 to 3.0 mass% Mg, 0.60 mass% or less Si, 0.8 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti.

5. 2. The food and beverage can lid according to claim 1, wherein the aluminum alloy contains 0.5 to 1.0 mass% Mn, 2.0 to 3.0 mass% Mg, 0.35 mass% or less Si, 0.6 mass% or less Fe, 0.25 mass% or less Cu, 0.10 mass% or less Cr, 0.25 mass% or less Zn, and 0.10 mass% or less Ti.

6. 6. A can lid for food and beverages according to claim 1, wherein the Mg content in the aluminum alloy is 2.0 to 3.0 mass %, and the remaining thickness of the score at the initial opening portion of the score is 71% or less of the original plate thickness.

7. 6. The food and beverage can lid according to claim 1, wherein the aluminum alloy plate made of the aluminum alloy has a tensile strength in the rolling 0° direction after paint baking of 350 to 410 MPa.

8. 6. A can lid for food and beverages according to claim 1, wherein the thickness of the unprocessed portion of the end is 0.19 to 0.30 mm, and the thickness of the unprocessed portion of the tab is 0.24 to 0.35 mm.

9. 6. The food and beverage can lid according to claim 1, wherein the aluminum alloy contains recycled material from used aluminum beverage cans.

10. 10. The food and beverage can lid according to claim 9, wherein the aluminum alloy has a Mn content of 0.8 to 1.4 mass %.

11. A food / beverage filled can, comprising a food / beverage can lid according to any one of claims 1 to 5 applied to a can filled with food / beverage.

Citation Information

Patent Citations

  • Sheath-core type composite fiber

    JP1983098426A

  • Pneumatic tire

    JP1984020705A

  • Al alloy sheet for tab having excellent repeated bendability and its manufacture

    JP1990149634A

  • Aluminum two piece can body and its manufacture

    JP1992221036A

  • Aluminum lid highly resistant to rupture under high internal pressure

    JP1995002248A